Pengaruh Kualitas Pelayanan Dan Kinerja Aparatur Pemerintah Desa Terhadap Kepuasan Masyarakat: Studi Kasus Balai Desa Bangsri, Bulakamba, Brebes - Vindi Astuti; Khalid Iskandar; Hendri Sucipto (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The problem that arises at this time is satisfaction with the service from the performance of government employees for the community, both at the village level to the national level. This research was conducted on the basis of problems that arise in the community from what they have received so far from Bangsri Village government services. Whether or not the community is satisfied is the direct experience of the community from service and employee performance for what has been obtained. This research was conducted in Bangsri Village, Bulakamba District, Brebes Regency from March 2023 to July 2023. The population in this study was 12,749 people and the sample for this study was 99 respondents. The testing tool and data analysis in this study used SPSS 26 with the method of testing and analysis through validity testing, reliability testing, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, t test, F test, Coefficient of Determination test. Results in this study shows that service quality has a significant effect on community satisfaction, as evidenced by the t value for variable X1 (4.671) greater than t table (1.661).The performance of village government officials has a significant effect on community satisfaction, this is evidenced by the t value calculated for variable X2 ( 2.936) is greater than t table (1.661) and the significant value of t X2 is less than 0.05 or 0.009 <0.05 Quality of service and performance of village government officials has a significant effect on community satisfaction, this result is indicated by a significant value of 0.000 greater than 0.05 and a calculated F value of 142.898 greater than F table 3.938 Service Quality and Performance of Village Government Apparatuses is able to predict the dependent variable, namely Community Satisfaction of 94.4%, the remaining 5.6% is explained by other variables outside this research.